Treatment of vascular lesions with balloon catheters. - Scialfa, G; Valsecchi, F; Scotti, G (American Journal of Neuroradiology, 1983)
During a 4 year period, 48 patients were treated with balloon catheters. There were 39 fistulas and nine aneurysms. Detachable balloons with a modified Debrun technique were used in 37 patients. Different kinds of technical problems were encountered. The arterial axis remained patent in 29 of the 37 fistulas; in the two mixed internal and external carotid-cavernous sinus fistulas, combined embolization with dura, isobutyl cyanoacrylate, and detachable balloon was used. In six of the nine aneurysms the arterial axis was occluded with a detachable balloon. In three of 48 patients, severe neurologic complications resulted in death.